The model of technology-supported learning for special educational needs learners (Motsel): promoting heutagogic-inclusive environment in Malaysian higher education / Roslinda Alias ... [et al.] (UiTM Press, 2019)
In this advent of technological era, computer-related devices such as notebook, tablet and smartphone are not considered as luxury tools anymore, instead it is a necessity for everyone to continue their life in this sophisticated age. Consequently, this scenario has changed human life – from the time they wake up in the morning until they go to bed at night. For instance, workplaces are becoming more complex in nature due to the technological advancement. To be a competent personnel does not necessarily lead ones to be capable in facing the rapid changes and complexities in workforce (Hase & Kenyon, 2007). Competencies is not enough in this 21st century and capability is important for the workers to survive in the complex work setting which requires them to be more creative, dynamic and innovative in nature.